Mangrove Cover Dynamics and Carbon Storage Estimation at Cemara Beach, West Lombok Regency - Lalu Auliya Akraboe Littaqwa; Muhsinun Muhsinun; Muh. Sahrul Ramdani; Wardatul Jannah; Legis Octaviana Saputri (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Mangrove ecosystems play an essential role in carbon sequestration and coastal protection. This study analyzes changes in mangrove cover and associated carbon storage at Cemara Beach, West Lombok Regency, using Sentinel-2 satellite imagery from 2019 and 2024. Supervised classification with the CART algorithm was applied through Google Earth Engine, supported by field verification and stakeholder interviews for management assessment. Results indicate an expansion of mangrove cover from 66,6 ha in 2019 to 71,63 ha in 2024, an increase of 4,97 ha (7,46%). Correspondingly, carbon stocks rose from 14.728,26 tons C to 16.252,45 tons C, with mangroves contributing the largest portion (over 62%). SWOT analysis showed strong ecological potential and supportive policies but highlighted challenges such as limited funding, land-use pressure, and low community awareness. Strengthening multi-stakeholder collaboration, environmental education, and sustainable rehabilitation programs is recommended to enhance ecological resilience and maximize blue carbon benefits.